2021 43rd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2021
DOI: 10.1109/embc46164.2021.9630287
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network Approach for Elbow Torque Estimation during Quasi-dynamic and Dynamic Contractions

Abstract: Accurate torque estimation during dynamic conditions is challenging, yet an important problem for many applications such as robotics, prosthesis control, and clinical diagnostics. Our objective is to accurately estimate the torque generated at the elbow during flexion and extension, under quasi-dynamic and dynamic conditions. High-density surface electromyogram (HD-EMG) signals, acquired from the long head and short head of biceps brachii, brachioradialis, and triceps brachii of five participants are used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…5). These findings are in line with a previous study by Hajian et al [13] that reported increased elbow torque prediction accuracy for isokinetic and dynamic tasks when using joint position and velocity in combination with EMG data. The need for diverse features in torque prediction of more complex movements might imply that the activation of surrounding muscles does not always fully determine joint torque.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5). These findings are in line with a previous study by Hajian et al [13] that reported increased elbow torque prediction accuracy for isokinetic and dynamic tasks when using joint position and velocity in combination with EMG data. The need for diverse features in torque prediction of more complex movements might imply that the activation of surrounding muscles does not always fully determine joint torque.…”
Section: Discussionsupporting
confidence: 93%
“…Comparable results between both approaches have been shown for ankle torque estimation during the isokinetic movement and gait [10] and knee joint torque estimation during non-weight bearing activities over seven days [11]. In particular, recurrent and convolutional neural networks (CNN) were found to perform well in EMG-informed estimation of biceps brachii muscle force in isometric contraction [12] and elbow joint torque during isotonic, isokinetic and dynamic task [13]. To achieve good results for increasingly more complex movements, such as dynamic tasks, artificial neural networks (ANN) require increasingly large training datasets, often resulting in a drop in estimation accuracy.…”
Section: Introductionmentioning
confidence: 96%
“…techniques with success, yet this input is not considered in this study as it, requires specialized equipment [10,11].…”
Section: Estimation Of Maximum Shoulder and Elbow Joint Torques Based...mentioning
confidence: 99%
“…Therefore, all subsequent references to 'EMG' specifically pertain to surface EMG. The majority of work thus far has focused on intra-subject force modeling, where user-specific models are developed using burdensome amounts of user-supplied data [2]- [9]. Recently, some studies have pooled data from multiple users to provide more data for deep inter-subject models [10]- [14], but the same users used to test the models were included during training.…”
Section: Introductionmentioning
confidence: 99%